Changes in hospitality workers' exposure to secondhand smoke following the implementation of New York's smoke-free law. Issue 4 (26th July 2005) - Farrelly, M C; Nonnemaker, J M; Chou, R; Hyland, A; Peterson, K K; Bauer, U E
Abstract : Objective: To assess the impact on hospitality workers' exposure to secondhand smoke of New York's smoke-free law that prohibits smoking in all places of employment, including restaurants, bars, and bowling facilities. Design: Pre-post longitudinal follow up design. Settings: Restaurants, bars, and bowling facilities in New York State. Subjects: At baseline, 104 non-smoking workers in restaurants, bars, and bowling facilities were recruited with newspaper ads, flyers, and radio announcements. Of these, 68 completed a telephone survey and provided at least one saliva cotinine specimen at baseline. At three, six, and 12 month follow up studies, 47, 38, and 32 workers from the baseline sample of 68 completed a telephone survey and provided at least one saliva cotinine specimen. Intervention: The smoke-free law went into effect 24 July 2003. Main outcome measures: Self reported sensory and respiratory symptoms and exposure to secondhand smoke; self administered saliva cotinine specimens. Analyses were limited to subjects in all four study periods who completed a telephone survey and provided at least one saliva cotinine specimen. Results: All analyses were limited to participants who completed both an interview and a saliva specimen for all waves of data collection (n  =  30) and who had cotinine concentrations ⩽ 15 ng/ml (n  =  24). Hours of exposure to secondhand smoke in hospitality jobs decreased from 12.1 hours (95% confidence interval (CI) 8.0 to 16.3 hours) to 0.2 hours (95% CI −0.1 to 0.5 hours) (p < 0.01) and saliva cotinine concentration decreased from 3.6 ng/ml (95% CI 2.6 to 4.7 ng/ml) to 0.8 ng/ml (95% CI 0.4 to 1.2 ng/ml) (p < 0.01) from baseline to the 12 month follow up. The prevalence of workers reporting sensory symptoms declined from 88% (95% CI 66% to 96%) to 38% (95% CI 20% to 59%) (p < 0.01); there was no change in the overall prevalence of upper respiratory symptoms (p < 0.16). Conclusion: New York's smoke-free law had its intended effect of protecting hospitality workers from exposure to secondhand smoke within three months of implementation. One year after implementation, the results suggest continued compliance with the law.